Transformational Leadership by The School Principal in The Implementation of Deep Learning at Sdn 10 Air Kumbang, Banyuasin - Intan Rosyita Al Fauziyah; Nurlina; Wahid Ibrahim Banul Ngindom (Graduate Program Magister Manajemen Pendidikan, 2026)
This study aims to analyze the transformational management of school principals in implementing deep learning at SDN 10 Air Kumbang Banyuasin. A descriptive qualitative approach was employed involving the principal, teachers, and school stakeholders selected through purposive sampling. Data were collected through in-depth interviews, observations, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that transformational management is implemented through participatory planning, teacher empowerment, coaching-based academic supervision, collaborative decision-making, and the development of an innovative school culture. These practices have strengthened teachers’ readiness to implement deep learning and improved instructional quality. Nevertheless, several challenges remain, including limited teacher understanding of deep learning concepts, uneven readiness for educational change, and inadequate learning facilities. This study contributes to educational management by integrating transformational leadership with POAC management functions as a strategic framework for implementing deep learning in primary schools.